Cytosolic DNA sensors activation of human astrocytes inhibits herpes simplex virus through IRF1 induction - Liu, Yu; Xu, Xi-Qiu; Li, Wei-Jing; Zhang, Biao; Meng, Feng-Zhen; Wang, Xu; Majid, Safah M.; Guo, Zihan; Ho, Wen-Zhe (Frontiers in Cellular and Infection Microbiology, 2024)
Introduction While astrocytes participate in the CNS innate immunity against herpes simplex virus type 1 (HSV-1) infection, they are the major target for the virus. Therefore, it is of importance to understand the interplay between the astrocyte-mediated immunity and HSV-1 infection. Methods Both primary human astrocytes and the astrocyte line (U373) were used in this study. RT-qPCR and Western blot assay were used to measure IFNs, the antiviral IFN-stimulated genes (ISGs), IFN regulatory factors (IRFs) and HSV-1 DNA. IRF1 knockout or knockdown was performed with CRISPR/Cas9 and siRNA transfection techniques. Results Poly(dA:dT) could inhibit HSV-1 replication and induce IFN-β/IFN-λs production in human astrocytes. Poly(dA:dT) treatment of astrocytes also induced the expression of the antiviral ISGs (Viperin, ISG56 and MxA). Among IRFs members examined, poly(dA:dT) selectively unregulated IRF1 and IRF9, particularly IRF1 in human astrocytes. The inductive effects of poly(dA:dT) on IFNs and ISGs were diminished in the IRF1 knockout cells. In addition, IRF1 knockout attenuated poly(dA:dT)-mediated HSV-1 inhibition in the cells. Conclusion The DNA sensors activation induces astrocyte intracellular innate immunity against HSV-1. Therefore, targeting the DNA sensors has potential for immune activation-based HSV-1 therapy.